Estudo da variabilidade genética de Ancylostoma caninum (Ercolani, 1859) parasito de Canis familiaris utilizando a técnica de RAPD - PCR - Hudson Andrade dos Santos (2000)
The genetic variability of Ancylostoma caninum was studied using RAPD molecular markers multisite Populations of three states of Minas Gerais, Belo Horizonte metropolitan region, southern Minas Gerais (Pocos de Caldas and Three Hearts) and the state of Espirito Santo (Vitoria ). Through the use of five primers (G06, G11, G15, G18 and M13-40 forward) were obtained from 56 polymorphic markers or not between 250 bp to 2036 bp. The DNA-POP program was used to calculate the proportion of bands shared between any of the specimens of A. caninum. This proportion was 78% ranging from 74% to 86% ^. There were no identical banding patterns among A. caninum studied. The number of bands shared was used to calculate the similarities and the values obtained a phenogram was constructed by UPGMA (unweighted arithmetic average) using the program MEGA (Molecular Evolutionary Genetics Analysis) version 1.01 developed by Kumar et al. (1993). Considering the merits of the individuals was observed that specimens of the same locality were more homogenous, which allowed them to group at least partly according to their geographical origin. There is greater than interpopulation variability within populations. The observer intrapopulation homogeneity was higher in the metropolitan region of Vitoria (ES), followed by metropolitan area of Belo Horizonte and then south of Minas Gerais. The phenogram showed the existence of two branches in the tree constructed, a sheltering people or groups in the metropolitan area of Belo Horizonte, and part of southern Ontario (Caldas0 Wells and the other housed a group of Vitoria (ES) and part of South de Minas Gerais (Three Hearts). The significance of the grouping of the population of southern Minas with Victoria remains unclear due to the lack of a better understanding of the genetics of this population. The RAPD technique proved to be an efficient tool study of genetic variability in A. caninum in different geographical areas separating the populations studied